Implementasi Komputasi Paralel dalam Pergerakan Lengan Robot Menggunakan Inverse Kinematic - Tezza Rangga Putra; Rizal Maulana; Wijaya Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The method of conventional robotic arm motion is by forward kinematic, which moves by determining the time of deviation of each joint to reach a point. Unlike the forward kinematic, inverse kinematics move by determining the angle required to perform a motion. Forward kinematics is considered as method that utilizes trial and error, this method become less effective because it takes a long time. Meanwhile, inverse kinematic offers more practical solution with more complex computing calculations. With the development of microcontroller complexity on calculation inverse kinematic can be done more quickly by using parallel computing that can take advantage of all the existing cores on the microcontroller. openMP is a C ++ program directory that describes the use of application program interfaces to perform parallel computations in multiple memory environments. openMP becomes one of the programs that can be utilized to perform parallel computing. The result is, openMP able to divide the program so that the Squential program imposes its process on core 1 (30.74%). But in the parallel program the process load fairly even distributed, although it looks more burdensome to core 2 (30,7%) and 3 (20,38%). Accuracy calculation results from both methods are same, both have same nois and error that is equal to 0.4 cm from x axis, 1.5 cm from y axis and 1.06 cm from z axis. In addition, the error also occurs at the servo angle, where the average error in 1st servo is 1o, at the 2nd servo is 1.24o, and at the 3rd servo is 4.1o. When compared to speed, the parallel method performs all tasks faster than squential by 20 seconds (36.4% of the sequential time) for 4 servos and 10 seconds (22.2% of the squared time) for 3 servos.